GE_GERICHTE P/3221/2020 vom 18. Januar 2023 - GE Cour de justice (2023)
DROIT PÉNAL DES MINEURS;TENTATIVE(DROIT PÉNAL);MEURTRE;PORNOGRAPHIE;DISPOSITIONS PÉNALES DE LA LARM | DPMIN; PPMIN; CP.133; CP.111; CP.22; CP.197; LARM